The Influence Of Training And Competency On Employee Performance At The Industrial Service Of Trade, Small And Medium Business Cooperatives In Riau Islands Province - Feby Indrani; Deden Trisnawijaya; Sabri (Citakonsultindo, 2023)
This study aims to determine the effect of training and competency on employee performance at the statistical informatics communication and coding department of Pekanbaru City. The method used is descriptive method. Collecting data using a list of statements or questionnaires filled out by the respondents. Then analyzed using multiple linear regression analysis.The results of multiple linear regression analysis produce a value of Y = 17.160 + 0.760 X1 + 0.598 X2 + e, which means that each discussion of the regression coefficient unit of the independent variable without adding the value of other variables, the performance increases according to the unit number of each variable. The results explain that the F test has a value of F-count ≥ F-table (36.154 greater than 3.22) and a significance level of 0.000 <0.005. This means that Training and Competence simultaneously have a significant effect on Employee performance.